Potensi Keagamaan pada Anak Usia Dini melalui Program MTQ Mahasiswa Kuliah Kerja Nyata di Desa Merangin, Kecamatan Kuok, Kabupaten Kampar Riau - Syahrul Hidayat; Tia Suherianti; Riva Mutiara; Ridho Aldiokta; Rizka Hasanah; Hasbullah Zakky; Chania Arnata; Afrina Putri; Fandi Rahmat; Mutiara Mutiara; Henni Syawal (MASPUL JOURNAL OF COMMUNITY EMPOWERMENT, 2022)
Musabaqah Tilawatil Quran is an Islamic festival in Indonesia that is usually carried out at the national level. Kukerta students of Riau University held a Musabaqah Tilawatil Quran Activity at the Merangin Village Level with the aim of strengthening Islamic values in children and adolescents. Musabaqah Tilawatil Qur'an activities were held at the Baiturrahman Mosque in Merangin Village, which was attended by children with an age range of 6-12 years and adolescent qualifications with an age of 14-17 years. Participants in the competition participated in the competition of tilawah, adhan, speech and continuation of verses. The success of this program is the enthusiasm of the children in displaying their abilities on stage with each competition attended by around 20 participants. Of course, this can train their mentality and responsiveness in front of crowded halayak. The presence of innovative activities carried out can make changes in a more advanced direction, especially in the religious aspect.